Method for preparing pre-lithiated graphene by recycling carbon-based negative electrode material
By recycling the lithium element in the carbon-based negative electrode material for prelithiation, and combining it with the Hummers redox method to prepare prelithiated graphene, the problem of particle cracking of lithium-ion battery negative electrode materials after long cycles has been solved, and resource recycling and Green and environmentally friendly preparation method.
Patent Information
- Application Number
- CN202310902096.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-20
AI Technical Summary
The particles of existing lithium-ion battery negative electrode materials crack after long cycles, resulting in a shortening of battery life and low recycling efficiency of waste lithium-ion batteries.
By recycling and removing impurities from the carbon-based negative electrode sheets, the lithium element contained in the recycled negative electrode material is used to achieve prelithiation of graphene, and the Hummers redox method is used to prepare prelithiated graphene.
It realizes resource recycling and reduces the risk of metal impurities in the preparation of traditional pre-lithiated graphene. The method is green, environmentally friendly and low-cost.
Smart Images

Figure CN119330348A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery negative electrode material recycling, and in particular to a method for recycling carbon-based negative electrode materials to prepare pre-lithiated graphene. Background Art
[0002] In recent years, the new energy industry has entered a stage of rapid development. According to data released by the Ministry of Industry and Information Technology, the national lithium-ion battery production will reach 750GWh in 2022. Although there have been many changes to the battery system to ensure the high energy density and long life of the new energy industry, the actual battery life is still mainly 3-5 years due to the characteristics of particle cracking after long cycles of the current main graphite negative electrode materials. According to statistics, the actual recycling volume of waste lithium-ion batteries in my country is 415,000 tons, a year-on-year increase of 75.8%, mainly in the recycling of batteries such as ternary and lithium cobalt oxide systems.
[0003] As a nanomaterial with stable crystallinity, excellent optical properties and excellent conductivity, graphene has a wide range of application prospects. Among the methods for preparing graphene, the Hummers redox method is the most common and can be used as a mass production process, and the product performance is relatively stable.
[0004] Pre-lithiated graphene electrode materials are usually prepared from pristine graphene materials via chemical synthesis methods or lithiation techniques combined with mechanical exfoliation techniques.
[0005] However, with the increasing awareness of sustainable development and environmental protection, researchers have been seeking new ways to promote the green production of graphene batteries. Recycling waste lithium-ion battery materials and reusing them for battery preparation is a promising and meaningful research direction. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing pre-lithiated graphene by recycling carbon-based negative electrode materials. By recycling and removing impurities from the carbon-based negative electrode plates, the lithium element contained in the recycled negative electrode materials can be used to achieve graphene pre-lithiation, thereby realizing resource recycling. The method proposed by the present invention is green and environmentally friendly and easy to implement.
[0007] To this end, an embodiment of the present invention provides a method for recycling carbon-based negative electrode materials to prepare pre-lithiated graphene, the method comprising:
[0008] The disassembled carbon-based negative electrode sheet is immersed in water, and then ultrasonically vibrated by an ultrasonic device to separate the negative electrode material from the negative electrode current collector, and then filtered to obtain a negative electrode carbon material slurry;
[0009] After drying the negative electrode carbon slurry, calcining at a temperature below 400° C. to obtain a sintered negative electrode carbon material;
[0010] The sintered negative electrode carbon material is added to dilute nitric acid with a concentration of less than 6 mol / L, stirred and allowed to stand to obtain a Li-containing + and acidic solutions of other metallic impurity ions;
[0011] Add cation exchange resin to the acidic solution, stir, adsorb other metal impurity ions through the cation exchange resin, and obtain Li-containing + and an acidic slurry of purified negative electrode carbon material;
[0012] The acidic slurry is used as a substrate and the pre-lithiated graphene is prepared by Hummers redox method.
[0013] Preferably, the temperature of the low-temperature calcination is 300-400° C., the insulation time is 2-4 hours, and air is introduced during the calcination process with a gas flow rate of 0.5-1 L / min.
[0014] Preferably, the immersion time is 2-4 hours, the ultrasonic duration is 0.5-1.5 hours, and the intensity is 30-50 KHz.
[0015] Preferably, in the preparation of the acidic solution, the concentration of the dilute nitric acid is 3 mol / L, the stirring speed is 100-150 r / min, the stirring time is 2-4 h, and the standing time is 2-4 h; the molar ratio of the added dilute nitric acid to the metal impurities contained in the recovered negative electrode carbon material is 2:1-3:1.
[0016] Preferably, the cation exchange resin is a strongly acidic cation exchange resin, wherein the strongly acidic cation exchange resin is a cation exchange resin whose main exchange group is a sulfonic acid group (-SO3H);
[0017] The molar ratio of the acidic functional groups in the cation exchange resin for replacing metal ions by exchange reaction to other metal impurity ions except lithium in the negative electrode carbon material is 1:1-2:1.
[0018] Preferably, in the preparation of the acidic slurry, the stirring speed is 100-150 r / min, and the stirring time is 2-4 h; the filtration is performed using a PE filter with a mesh size of 100 meshes.
[0019] Preferably, the method further comprises: soaking and washing the cation exchange resin after adsorbing other metal impurity ions in dilute nitric acid.
[0020] Further preferably, the concentration of the dilute nitric acid is between 0.5 mol / L and 1 mol / L.
[0021] The method for preparing pre-lithiated graphene provided by the embodiment of the present invention oxidizes the surface of carbon-based material particles by low-temperature calcination in an air atmosphere, thereby forming pores, which can facilitate the peeling of graphite sheets and volatilize components such as binders and electrolytes attached to the surface of carbon-based materials, which is more conducive to metal impurity removal; by using cation exchange resins, metal impurities in recycled negative electrode materials can be effectively removed, and the cation exchange resins after impurity removal can still be regenerated after being soaked and rinsed in dilute nitric acid; pre-lithiation can be carried out using the lithium element contained in the recycled negative electrode materials, and in the oxidation-reduction process, lithium ions are more likely to combine with oxygen-containing functional groups of graphene oxide, thereby achieving pre-lithiation, and thus pre-lithiated graphene is directly prepared by the Hummers oxidation-reduction method; the method is green, environmentally friendly, and low-cost, and reduces the risk of metal impurities introduced from the outside in the traditional preparation of pre-lithiated graphene. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A flow chart of a method for recycling carbon-based negative electrode materials to prepare pre-lithiated graphene provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.
[0024] The embodiment of the present invention provides a method for recycling carbon-based negative electrode materials to prepare pre-lithiated graphene, the main steps of which are as follows: Figure 1 As shown, including:
[0025] Step 110, soaking the disassembled carbon-based negative electrode sheet in water, and then using an ultrasonic device to perform ultrasonic oscillation to separate the negative electrode material from the negative electrode current collector, and filtering to obtain a negative electrode carbon material slurry;
[0026] Among them, the immersion time is 2-4h, the ultrasonic duration is 0.5-1.5h, and the intensity is 30-50KHz.
[0027] The lithium element contained in the negative electrode carbon material refers to the lithium element embedded in the negative electrode to be recycled. Generally, the mass fraction of lithium element in the negative electrode carbon material is 0.5%-1.5%. In addition to lithium ions, the negative electrode carbon material also contains some other metal impurity ions.
[0028] Step 120, drying the negative electrode carbon slurry and then calcining it at a temperature below 400° C. to obtain a sintered negative electrode carbon material;
[0029] The temperature of low-temperature calcination is 300-400°C, the insulation time is 2-4 hours, and air is introduced during the calcination process with a gas flow rate of 0.5-1 L / min.
[0030] Step 130, adding the sintered negative electrode carbon material to dilute nitric acid with a concentration of less than 6 mol / L, stirring and then standing to obtain a solution containing Li + and acidic solutions of other metallic impurity ions;
[0031] Among them, the concentration of dilute nitric acid is preferably 3 mol / L, the stirring speed is 100-150r / min, the stirring time is 2-4h, and the standing time is 2-4h; the molar ratio of the added dilute nitric acid to the metal impurities contained in the recovered negative electrode carbon material is 2:1-3:1.
[0032] Step 140, add cation exchange resin to the acidic solution, stir, adsorb other metal impurity ions through the cation exchange resin, and obtain Li-containing + and an acidic slurry of purified negative electrode carbon material;
[0033] Preferably, the cation exchange resin is a strongly acidic cation exchange resin, which is a cation exchange resin whose main exchange group is a sulfonic acid group (-SO3H).
[0034] The total exchange capacity of the cation exchange resin, that is, the molar ratio of the acidic functional groups in the cation exchange resin used for the exchange reaction to replace the metal ions to the other metal impurity ions in the negative electrode carbon material except lithium is 1:1-2:1.
[0035] In the preparation of the acidic slurry, the stirring speed is 100-150 r / min, and the stirring time is 2-4 hours; the filtration is carried out using a polyethylene (PE) filter with a mesh size of 100 meshes.
[0036] After this step, the cation exchange resin after adsorbing other metal impurity ions can also be soaked and rinsed in dilute nitric acid, wherein the concentration of the dilute nitric acid is between 0.5 mol / L and 1 mol / L, so as to recycle the cation exchange resin.
[0037] Step 150, using the acidic slurry as a substrate, and adopting the Hummers redox method to prepare pre-lithiated graphene.
[0038] The Hummers redox method is a conventional existing method and will not be introduced here. The present invention utilizes this method to prepare pre-lithiated graphene, mainly using an acidic slurry as a substrate to mix it with concentrated sulfuric acid, and adding a strong oxidant and stirring. During this process, oxidation occurs to generate pre-lithiated graphene oxide. During the oxidation process, factors such as the concentration of sulfuric acid, the amount of strong oxidant added, the reaction time and temperature can be adjusted to control the oxygen content of the generated graphene oxide. Finally, the oxidized product is washed and filtered multiple times to remove unreacted acid and generated oxide residues.
[0039] The method for preparing pre-lithiated graphene provided by the embodiment of the present invention oxidizes the surface of carbon-based material particles by low-temperature calcination in an air atmosphere, thereby forming pores, which can facilitate the peeling of graphite sheets and volatilize components such as binders and electrolytes attached to the surface of carbon-based materials, which is more conducive to metal impurity removal; by using cation exchange resins, metal impurities in recycled negative electrode materials can be effectively removed, and the cation exchange resins after impurity removal can still be regenerated after being soaked and rinsed in dilute nitric acid; pre-lithiation can be carried out using the lithium element contained in the recycled negative electrode materials, and in the oxidation-reduction process, lithium ions are more likely to combine with oxygen-containing functional groups of graphene oxide, thereby achieving pre-lithiation, and thus pre-lithiated graphene is directly prepared by the Hummers oxidation-reduction method; the method is green, environmentally friendly, and low-cost, and reduces the risk of metal impurities introduced from the outside in the traditional preparation of pre-lithiated graphene.
[0040] In order to more clearly illustrate the purpose and advantages of the present invention, the present invention is further described below in conjunction with the embodiments. In addition, the embodiments described in the present invention are only some embodiments. Based on the embodiments described in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the protection scope of the present invention.
[0041] Example 1
[0042] 1) Soak the disassembled lithium battery negative electrode material pole piece in water for 2 hours, and vibrate it with an ultrasonic device for 1 hour at an intensity of 40KHz. After filtering, dry the negative electrode carbon material slurry. After drying, test the moisture content by weight loss method to ≤0.1%. The dried negative electrode carbon material is calcined at a low temperature, the sintering temperature is set at 300°C, the insulation time is 2 hours, and the air gas flow rate is 0.5L / min. The calcined negative electrode carbon material contains a lithium element mass fraction of 0.5%.
[0043] 2) Add the calcined negative electrode carbon material to dilute nitric acid with a concentration of 3 mol / L, stir thoroughly, stir at a speed of 120 r / min, stir for 2 h, the molar ratio of the added nitric acid to the metal impurities contained in the calcined negative electrode carbon material is 2:1, stand for 2 h, and obtain an acidic solution for recovering the negative electrode carbon material.
[0044] 3) Add a strong acid cation exchange resin containing a sulfonic acid group (-SO3H) to the acidic solution of the recovered negative electrode carbon material, the molar ratio of the total exchange capacity of the added strong acid cation exchange resin to the other metal impurities contained in the recovered negative electrode carbon material except lithium is 1:1, stir to make it fully react, the stirring speed is 120r / min, the stirring time is 2h, and filter by PE filter with a mesh size of 100 to obtain a solution containing Li +and an acidic slurry of purified negative electrode carbon material.
[0045] 4) Containing Li + The pre-lithium graphene is prepared by using the Hummer redox method with the acidic slurry of the purified negative electrode carbon material as the substrate. The specific method is as follows:
[0046] Slowly add concentrated sulfuric acid of equal molar mass to the acidic slurry, and continue stirring, while controlling the slurry temperature at 20-30°C. After stirring evenly, slowly add potassium permanganate solid with a molar mass ratio of 2.5:1 to concentrated sulfuric acid, stir for 30min, then add a 3% hydrogen peroxide solution with a molar mass ratio of 1:5 to potassium permanganate, stir for 30min until no bubbles are generated, heat the solution to 80°C using a water bath method, add hydrazine hydrate with a molar ratio of 1:400 to the recovered negative electrode carbon material, stir for 12h, rinse with methanol and water several times and then dry to obtain pre-lithium graphene.
[0047] Testing of pre-lithium graphene materials:
[0048] Preparation of negative electrode material: A low-graphitization material with a capacity of 330 mAh / g and a first-cycle efficiency of 80% is mixed with the prepared pre-lithiated graphene in a mass ratio of 1:1.
[0049] This test was conducted on a CR2032 button cell, mainly involving materials: lithium sheet, electrolyte (1 mol / L lithium hexafluorophosphate @ ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate in a volume ratio of 1:1:1:1), polyethylene (PE) base film and the negative electrode material prepared by the present invention. The button cell test procedure was 0.1C discharge to 5mV, 0.02C discharge to 5mV, and 0.1C charge to 2V.
[0050] Example 2
[0051] 1) Soak the disassembled lithium battery negative electrode material pole piece in water for 2 hours, and vibrate it with an ultrasonic device for 1 hour at an intensity of 40KHz. After filtering, dry the negative electrode carbon material slurry. After drying, test the moisture content by weight loss method to ≤0.1%. The dried negative electrode carbon material is calcined at a low temperature, the sintering temperature is set to 350°C, the insulation time is 2 hours, and the air gas flow rate is 1.0L / min. The calcined negative electrode carbon material contains a lithium element mass fraction of 0.5%.
[0052] 2) Add the calcined negative electrode carbon material to dilute nitric acid with a concentration of 3 mol / L, stir thoroughly, stir at a speed of 120 r / min, stir for 3 h, add nitric acid and the molar ratio of the metal impurities contained in the calcined negative electrode carbon material is 2:1, stand for 4 h, and obtain an acidic solution for recovering the negative electrode carbon material.
[0053] 3) Adding the strong acidic cation exchange resin of Example 1 to the acidic solution of the recovered negative electrode carbon material, the molar ratio of the total exchange capacity of the added strong acidic cation exchange resin to the other metal impurities contained in the recovered negative electrode carbon material except lithium is 1:1, stirring to make it fully react, the stirring speed is 120r / min, the stirring time is 2h, and the PE filter is used for filtering, the filter mesh number is 100 mesh, and the Li-containing solution is obtained. + and an acidic slurry of purified negative electrode carbon material.
[0054] 4) Containing Li + The pre-lithium graphene is prepared by using the Hummer redox method with the acidic slurry of the purified negative electrode carbon material as the substrate. The specific method is as follows:
[0055] Slowly add concentrated sulfuric acid of equal molar mass to the acidic slurry, and continue stirring, while controlling the slurry temperature at 20-30°C. After stirring evenly, slowly add potassium permanganate solid with a molar mass ratio of 2.5:1 to concentrated sulfuric acid, stir for 30min, then add a 3% hydrogen peroxide solution with a molar mass ratio of 1:5 to potassium permanganate, stir for 30min until no bubbles are generated, heat the solution to 80°C using a water bath method, add hydrazine hydrate with a molar ratio of 1:400 to the recovered negative electrode carbon material, stir for 12h, rinse with methanol and water several times and then dry to obtain pre-lithium graphene.
[0056] The testing method for the pre-lithiation graphene material is the same as that in Example 1.
[0057] Example 3
[0058] 1) Soak the disassembled lithium battery negative electrode material pole piece in water for 2 hours, and vibrate it with an ultrasonic device for 1 hour at an intensity of 40KHz. After filtering, dry the negative electrode carbon material slurry. After drying, test the moisture content by weight loss method to ≤0.1%. The dried negative electrode carbon material is calcined at a low temperature, the sintering temperature is set at 400°C, the insulation time is 4 hours, and the air gas flow rate is 1.0L / min. The calcined negative electrode carbon material contains a lithium element mass fraction of 0.5%.
[0059] 2) Add the calcined negative electrode carbon material to dilute nitric acid with a concentration of 3 mol / L, stir thoroughly, stir at a speed of 120 r / min, stir for 4 h, add nitric acid and the molar ratio of the metal impurities contained in the calcined negative electrode carbon material is 2:1, stand for 4 h, and obtain an acidic solution for recovering the negative electrode carbon material.
[0060] 3) Adding the strong acidic cation exchange resin of Example 1 to the acidic solution of the recovered negative electrode carbon material, the molar ratio of the total exchange capacity of the added strong acidic cation exchange resin to the other metal impurities contained in the recovered negative electrode carbon material except lithium is 1:1, stirring to make it fully react, the stirring speed is 120r / min, the stirring time is 2h, and the PE filter is used for filtering, the filter mesh number is 100 mesh, and the Li-containing solution is obtained. + and an acidic slurry of purified negative electrode carbon material.
[0061] 4) Containing Li + The pre-lithium graphene is prepared by using the Hummer redox method with the acidic slurry of the purified negative electrode carbon material as the substrate. The specific method is as follows:
[0062] Slowly add concentrated sulfuric acid of equal molar mass to the acidic slurry, and continue stirring, while controlling the slurry temperature at 20-30°C. After stirring evenly, slowly add potassium permanganate solid with a molar mass ratio of 2.5:1 to concentrated sulfuric acid, stir for 30min, then add a 3% hydrogen peroxide solution with a molar mass ratio of 1:5 to potassium permanganate, stir for 30min until no bubbles are generated, heat the solution to 80°C using a water bath method, add hydrazine hydrate with a molar ratio of 1:400 to the recovered negative electrode carbon material, stir for 12h, rinse with methanol and water several times and then dry to obtain pre-lithium graphene.
[0063] The testing method for the pre-lithiation graphene material is the same as that in Example 1.
[0064] Example 4
[0065] 1) Soak the disassembled lithium battery negative electrode material pole piece in water for 2 hours, and vibrate it with an ultrasonic device for 1 hour at an intensity of 40KHz. After filtering, dry the negative electrode carbon material slurry. After drying, test the moisture content by weight loss method to ≤0.1%. The dried negative electrode carbon material is calcined at a low temperature, the sintering temperature is set at 400°C, the insulation time is 4 hours, and the air gas flow rate is 1.0L / min. The calcined negative electrode carbon material contains a lithium element mass fraction of 0.5%.
[0066] 2) Add the calcined negative electrode carbon material to dilute nitric acid with a concentration of 3 mol / L, stir thoroughly, stir at a speed of 120 r / min, stir for 4 h, add nitric acid and the molar ratio of the metal impurities contained in the calcined negative electrode carbon material is 3:1, stand for 4 h, and obtain an acidic solution for recovering the negative electrode carbon material.
[0067] 3) Adding the strong acidic cation exchange resin of Example 1 to the acidic solution of the recovered negative electrode carbon material, the molar ratio of the total exchange capacity of the added strong acidic cation exchange resin to the other metal impurities contained in the recovered negative electrode carbon material except lithium is 1:1, stirring to make it fully react, the stirring speed is 120r / min, the stirring time is 2h, and the PE filter is used for filtering, the filter mesh number is 100 mesh, and the Li-containing solution is obtained. + and an acidic slurry of purified negative electrode carbon material.
[0068] 4) Containing Li + The pre-lithium graphene is prepared by using the Hummer redox method with the acidic slurry of the purified negative electrode carbon material as the substrate. The specific method is as follows:
[0069] Slowly add concentrated sulfuric acid of equal molar mass to the acidic slurry, and continue stirring, while controlling the slurry temperature at 20-30°C. After stirring evenly, slowly add potassium permanganate solid with a molar mass ratio of 2.5:1 to concentrated sulfuric acid, stir for 30min, then add a 3% hydrogen peroxide solution with a molar mass ratio of 1:5 to potassium permanganate, stir for 30min until no bubbles are generated, heat the solution to 80°C using a water bath method, add hydrazine hydrate with a molar ratio of 1:400 to the recovered negative electrode carbon material, stir for 12h, rinse with methanol and water several times and then dry to obtain pre-lithium graphene.
[0070] The testing method for the pre-lithiation graphene material is the same as that in Example 1.
[0071] Example 5
[0072] 1) Soak the disassembled lithium battery negative electrode material pole piece in water for 2 hours, and vibrate it with an ultrasonic device for 1 hour at an intensity of 40KHz. After filtering, dry the negative electrode carbon material slurry. After drying, test the moisture content by weight loss method to ≤0.1%. The dried negative electrode carbon material is calcined at a low temperature, the sintering temperature is set at 400°C, the insulation time is 4 hours, and the air gas flow rate is 1.0L / min. The calcined negative electrode carbon material contains a lithium element mass fraction of 0.5%.
[0073] 2) Add the calcined negative electrode carbon material to dilute nitric acid with a concentration of 3 mol / L, stir thoroughly, stir at a speed of 120 r / min, stir for 4 h, add nitric acid and the molar ratio of the metal impurities contained in the calcined negative electrode carbon material is 3:1, stand for 4 h, and obtain an acidic solution for recovering the negative electrode carbon material.
[0074] 3) Adding the strong acid cation exchange resin of Example 1 to the acidic solution of the recovered negative electrode carbon material, the molar ratio of the total exchange capacity of the added strong acid cation exchange resin to the other metal impurities contained in the recovered negative electrode carbon material except lithium is 2:1, stirring to make it fully react, the stirring speed is 120r / min, the stirring time is 3h, and filtering is carried out in the form of PE filter with a mesh size of 100 to obtain Li-containing + and an acidic slurry of purified negative electrode carbon material.
[0075] 4) Containing Li + The pre-lithium graphene is prepared by using the Hummer redox method with the acidic slurry of the purified negative electrode carbon material as the substrate. The specific method is as follows:
[0076] Slowly add concentrated sulfuric acid of equal molar mass to the acidic slurry, and continue stirring, while controlling the slurry temperature at 20-30°C. After stirring evenly, slowly add potassium permanganate solid with a molar mass ratio of 2.5:1 to concentrated sulfuric acid, stir for 30min, then add a 3% hydrogen peroxide solution with a molar mass ratio of 1:5 to potassium permanganate, stir for 30min until no bubbles are generated, heat the solution to 80°C using a water bath method, add hydrazine hydrate with a molar ratio of 1:400 to the recovered negative electrode carbon material, stir for 12h, rinse with methanol and water several times and then dry to obtain pre-lithium graphene.
[0077] The testing method for the pre-lithiation graphene material is the same as that in Example 1.
[0078] Example 6
[0079] 1) Soak the disassembled lithium battery negative electrode material pole piece in water for 2 hours, and vibrate it with an ultrasonic device for 1 hour at an intensity of 40KHz. After filtering, dry the negative electrode carbon material slurry. After drying, test the moisture content by weight loss method to ≤0.1%. The dried negative electrode carbon material is calcined at a low temperature, the sintering temperature is set at 400°C, the insulation time is 4 hours, and the air gas flow rate is 1.0L / min. The calcined negative electrode carbon material contains a lithium element mass fraction of 0.5%.
[0080] 2) Add the calcined negative electrode carbon material to dilute nitric acid with a concentration of 3 mol / L, stir thoroughly, stir at a speed of 120 r / min, stir for 4 h, add nitric acid and the molar ratio of the metal impurities contained in the calcined negative electrode carbon material is 3:1, stand for 4 h, and obtain an acidic solution for recovering the negative electrode carbon material.
[0081] 3) Adding the strong acidic cation exchange resin of Example 1 to the acidic solution of the recovered negative electrode carbon material, the molar ratio of the total exchange capacity of the added strong acidic cation exchange resin to the other metal impurities contained in the recovered negative electrode carbon material except lithium is 2:1, stirring to make it fully react, the stirring speed is 120r / min, the stirring time is 4h, and the PE filter is used for filtering, the filter mesh number is 100 mesh, and the Li-containing solution is obtained. + and an acidic slurry of purified negative electrode carbon material.
[0082] 4) Containing Li + The pre-lithium graphene is prepared by using the Hummer redox method with the acidic slurry of the purified negative electrode carbon material as the substrate. The specific method is as follows:
[0083] Slowly add concentrated sulfuric acid of equal molar mass to the acidic slurry, and continue stirring, while controlling the slurry temperature at 20-30°C. After stirring evenly, slowly add potassium permanganate solid with a molar mass ratio of 2.5:1 to concentrated sulfuric acid, stir for 30min, then add a 3% hydrogen peroxide solution with a molar mass ratio of 1:5 to potassium permanganate, stir for 30min until no bubbles are generated, heat the solution to 80°C using a water bath method, add hydrazine hydrate with a molar ratio of 1:400 to the recovered negative electrode carbon material, stir for 12h, rinse with methanol and water several times and then dry to obtain pre-lithium graphene.
[0084] The testing method for the pre-lithiation graphene material is the same as that in Example 1.
[0085] Example 7
[0086] 1) Soak the disassembled lithium battery negative electrode material pole piece in water for 2 hours, use an ultrasonic device to vibrate, the ultrasonic duration is 1 hour, the intensity is 40KHz, and after filtering, the negative electrode carbon material slurry is dried. After drying, the water content is tested by weight loss method ≤ 0.1%. The dried negative electrode carbon material is calcined at low temperature, the sintering temperature is set to 400°C, the insulation time is 4 hours, and the air gas flow rate is 1.0L / min. The calcined negative electrode carbon material contains a lithium element mass fraction of 1.0%.
[0087] 2) Add the calcined negative electrode carbon material to dilute nitric acid with a concentration of 3 mol / L, stir thoroughly, stir at a speed of 120 r / min, stir for 4 h, add nitric acid and the molar ratio of the metal impurities contained in the calcined negative electrode carbon material is 3:1, stand for 4 h, and obtain an acidic solution for recovering the negative electrode carbon material.
[0088] 3) Adding the strong acidic cation exchange resin of Example 1 to the acidic solution of the recovered negative electrode carbon material, the molar ratio of the total exchange capacity of the added strong acidic cation exchange resin to the other metal impurities contained in the recovered negative electrode carbon material except lithium is 2:1, stirring to make it fully react, the stirring speed is 120r / min, the stirring time is 4h, and the PE filter is used for filtering, the filter mesh number is 100 mesh, and the Li-containing solution is obtained. + and an acidic slurry of purified negative electrode carbon material.
[0089] 4) Containing Li + The pre-lithium graphene is prepared by using the Hummer redox method with the acidic slurry of the purified negative electrode carbon material as the substrate. The specific method is as follows:
[0090] Slowly add concentrated sulfuric acid of equal molar mass to the acidic slurry, and continue stirring, while controlling the slurry temperature at 20-30°C. After stirring evenly, slowly add potassium permanganate solid with a molar mass ratio of 2.5:1 to concentrated sulfuric acid, stir for 30min, then add a 3% hydrogen peroxide solution with a molar mass ratio of 1:5 to potassium permanganate, stir for 30min until no bubbles are generated, heat the solution to 80°C using a water bath method, add hydrazine hydrate with a molar ratio of 1:400 to the recovered negative electrode carbon material, stir for 12h, rinse with methanol and water several times and then dry to obtain pre-lithium graphene.
[0091] The testing method for the pre-lithiation graphene material is the same as that in Example 1.
[0092] Example 8
[0093] 1) Soak the disassembled lithium battery negative electrode material pole piece in water for 2 hours, and vibrate it with an ultrasonic device for 1 hour at an intensity of 40KHz. After filtering, dry the negative electrode carbon material slurry. After drying, test the moisture content by weight loss method to ≤0.1%. The dried negative electrode carbon material is calcined at a low temperature, the sintering temperature is set at 400°C, the insulation time is 4 hours, and the air gas flow rate is 1.0L / min. The calcined negative electrode carbon material contains a lithium element mass fraction of 1.5%.
[0094] 2) Add the calcined negative electrode carbon material to dilute nitric acid with a concentration of 3 mol / L, stir thoroughly, stir at a speed of 120 r / min, stir for 4 h, add nitric acid and the molar ratio of the metal impurities contained in the calcined negative electrode carbon material is 3:1, stand for 4 h, and obtain an acidic solution for recovering the negative electrode carbon material.
[0095] 3) Adding the strong acidic cation exchange resin of Example 1 to the acidic solution of the recovered negative electrode carbon material, the molar ratio of the total exchange capacity of the added strong acidic cation exchange resin to the other metal impurities contained in the recovered negative electrode carbon material except lithium is 2:1, stirring to make it fully react, the stirring speed is 120r / min, the stirring time is 4h, and the PE filter is used for filtering, the filter mesh number is 100 mesh, and the Li-containing solution is obtained. + and an acidic slurry of purified negative electrode carbon material.
[0096] 4) Containing Li + The pre-lithium graphene is prepared by using the Hummer redox method with the acidic slurry of the purified negative electrode carbon material as the substrate. The specific method is as follows:
[0097] Slowly add concentrated sulfuric acid of equal molar mass to the acidic slurry, and continue stirring, while controlling the slurry temperature at 20-30°C. After stirring evenly, slowly add potassium permanganate solid with a molar mass ratio of 2.5:1 to concentrated sulfuric acid, stir for 30min, then add a 3% hydrogen peroxide solution with a molar mass ratio of 1:5 to potassium permanganate, stir for 30min until no bubbles are generated, heat the solution to 80°C using a water bath method, add hydrazine hydrate with a molar ratio of 1:400 to the recovered negative electrode carbon material, stir for 12h, rinse with methanol and water several times and then dry to obtain pre-lithium graphene.
[0098] The test results of the above embodiments are shown in Table 1 below.
[0099] serial number Capacity (mAh / g) First week efficiency (%) Example 1 385.1 82.3 Example 2 387.6 82.5 Example 3 390.3 82.9 Example 4 391.5 84.2 Example 5 390.6 85.1 Example 6 391.7 86.3 Example 7 391.2 88.1 Example 8 390.9 91.2
[0100] Table 1
[0101] It can be seen that the pre-lithiated graphene prepared in the above embodiments of the present invention has the effects of high initial efficiency and high capacity as the negative electrode material of lithium-ion batteries.
[0102] The method for recycling carbon-based negative electrode materials to prepare pre-lithiated graphene proposed in the present invention has broad application prospects in lithium-ion battery material recycling and graphene material preparation.
[0103] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for recycling carbon-based negative electrode materials to prepare pre-lithiated graphene, characterized in that: The method comprises: The disassembled carbon-based negative electrode sheet is immersed in water, and then ultrasonically vibrated by an ultrasonic device to separate the negative electrode material from the negative electrode current collector, and then filtered to obtain a negative electrode carbon material slurry; After drying the negative electrode carbon slurry, calcining at a temperature below 400° C. to obtain a sintered negative electrode carbon material; The sintered negative electrode carbon material is added to dilute nitric acid with a concentration of less than 6 mol / L, stirred and allowed to stand to obtain a Li + and acidic solutions of other metallic impurity ions; Add cation exchange resin to the acidic solution, stir, adsorb other metal impurity ions through the cation exchange resin, and obtain Li + and an acidic slurry of purified negative electrode carbon material; The acidic slurry is used as a substrate and the pre-lithiated graphene is prepared by Hummers redox method.
2. The method for preparing pre-lithiated graphene according to claim 1, characterized in that: The immersion time is 2-4 hours, the ultrasound duration is 0.5-1.5 hours, and the intensity is 30-50 KHz.
3. The method for preparing pre-lithiated graphene according to claim 1, characterized in that: The temperature of the low-temperature calcination is 300-400° C., the insulation time is 2-4 hours, and air is introduced during the calcination process with a gas flow rate of 0.5-1 L / min.
4. The method for preparing pre-lithiated graphene according to claim 1, characterized in that: In the preparation of the acidic solution, the concentration of the dilute nitric acid is 3 mol / L, the stirring speed is 100-150 r / min, the stirring time is 2-4 h, and the standing time is 2-4 h; the molar ratio of the added dilute nitric acid to the metal impurities contained in the recovered negative electrode carbon material is 2:1-3:
1.
5. The method for preparing pre-lithiated graphene according to claim 1, characterized in that: The cation exchange resin is a strongly acidic cation exchange resin, wherein the strongly acidic cation exchange resin is a cation exchange resin whose main exchange group is a sulfonic acid group (-SO3H); The molar ratio of the acidic functional groups in the cation exchange resin for replacing metal ions by exchange reaction to other metal impurity ions except lithium in the negative electrode carbon material is 1:1-2:
1.
6. The method for preparing pre-lithiated graphene according to claim 1, characterized in that: In the preparation of the acidic slurry, the stirring speed is 100-150 r / min, and the stirring time is 2-4 h; the filtration is performed using a PE filter with a mesh size of 100 meshes.
7. The method for preparing pre-lithiated graphene according to claim 1, characterized in that: The method further comprises: soaking and washing the cation exchange resin after adsorbing other metal impurity ions in dilute nitric acid.
8. The method for preparing pre-lithiated graphene according to claim 7, characterized in that: The concentration of the dilute nitric acid is between 0.5 mol / L and 1 mol / L.
Citation Information
Patent Citations
Method for separating lithium and graphite from negative electrode material of waste lithium battery and resource utilization
CN105355996A
Recycling method of decommissioned lithium ion battery negative electrode graphite
CN111924836A
Pre-lithiated negative pole piece, and preparation method thereof and lithium secondary battery
CN112825350A
Method for recycling graphite negative electrode of waste battery
CN113200541A
Pre-lithiated graphene as well as preparation method and application thereof
CN113540448A